Self-esteem and organizational values in university students and not university students from Lima - Loli Pineda, Alejandro E. (2002)
The selfesteem and the organizationals values in university students and not university students of Lima, is a study developed in a sample of 3215 students belonging to four universities of Lima; and not students conformed by egressions, professional and postgraduados, many of which show off directive charges in public or private companies, with the purpose to know the existing relation among the selfesteem and the values organizational of the same, in Lima Metropolitan, and to determine the differences among the autoestima and certain demographics characteristics. The results indicate that the university students give greater importance to the values as service to the client, the cleaning, and to the quality of the product and of the service, and smaller importance to the honesty, to the respect to the person and to the responsibility; while the not students offer greater importance to the service to the client, cleaning and confidence, and smaller importance to honesty. This same hierarchy is observed when is established the relation with the selfesteem, above all, when the selfesteem is very drop, lowers or intermediate; while when the selfesteem is high or very high is located in the first place the cleaning and improvement the puntualidad to being located in the fourth place in importance, this is a value that improves to the extent that the selfesteem is elevated. Likewise, they are found differentiates significant when is compared the selfesteem and some demographics characteristics such as the origin, the kind, the civil state as the age.